2021
DOI: 10.1111/plb.13235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uniconazole and nitrogen level on lodging resistance and yield potential of maize under medium and high plant density

Abstract: Lodging in maize results in grain yield reduction. This experiment investigated the effects of different application rates of the growth retardant, uniconazole (UCZ), and nitrogen (N) on medium and high maize population densities on lodging resistance and yield. UCZ was applied to maize seeds at concentrations of 0 (U0) and 25 (U25) mg kg−1, and three different N application rates, 0 (N0), 150 (N150) and 225 (N225) kg ha−1, at plant densities of 75,000 (D1) and 105,000 plants ha−1 (D2). UCZ application, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Despite of the enhanced resistance to F. verticillioides in Arabidopsis with overaccumulation ofAtGA2ox7 , many adverse effects were also occurred on development, such as dwarf plants and delayed flowering (Figure 4A), which would be likely expected in maize. In addition, it has been reported that application of GA inhibitor uniconazole significantly reduced lodging rate and enhanced yield in maize (Ahmad et al, 2021). Our data also showed the positive effects of uniconazole on F. verticillioidesresistance and dwarf traits in maize and rice (Figure 8C-E and Figure S6).…”
Section: Discussionsupporting
confidence: 82%
“…Despite of the enhanced resistance to F. verticillioides in Arabidopsis with overaccumulation ofAtGA2ox7 , many adverse effects were also occurred on development, such as dwarf plants and delayed flowering (Figure 4A), which would be likely expected in maize. In addition, it has been reported that application of GA inhibitor uniconazole significantly reduced lodging rate and enhanced yield in maize (Ahmad et al, 2021). Our data also showed the positive effects of uniconazole on F. verticillioidesresistance and dwarf traits in maize and rice (Figure 8C-E and Figure S6).…”
Section: Discussionsupporting
confidence: 82%
“…Melatonin has been discovered to increase photosynthetic carbon assimilation and antioxidant enzyme activity in maize under abiotic stress conditions [ 28 ]. Maize growth and productivity are hampered by a lack of nitrogen [ 29 ]. However, to date, few studies have explored the performance and function of melatonin combined with nitrogen-based on evaluation and N absorption of metabolism in cereal crops under drought-stress conditions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Uniconazole is widely applied to control plant height and enhance plant lodging resistance ( Ahmad et al., 2021a ; Lv et al., 2022 ). In this study, uniconazole treatment remarkably inhibited hypocotyl elongation and increased the hypocotyl diameter of flowering Chinese cabbage seedlings ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has a shorter degradation cycle and less application dosage, and it is more environmentally friendly ( Tao et al., 1997 ). Previous reports showed that uniconazole is widely applied to control plant height and enhance plant lodging resistance ( Ahmad et al., 2021a ; Lv et al., 2022 ). To date, uniconazole treatment in the process of intensive vegetable seedling cultivation mostly focuses on the screening of the application concentration ( Zuo et al., 2020 ), and there is little information about its molecular regulatory mechanism.…”
Section: Introductionmentioning
confidence: 99%